Efflux pumps of Gram-negative bacteria: what they do, how they do it, with what and how to deal with them - Amaral, Leonard (Frontiers Media S.A., 2014)
This review discusses the relationship of the efflux pump (EP) system of Gram-negative bacteria to other antibiotic resistance mechanisms of the bacterium such as quorum sensing, biofilms, two component regulons, etc. The genetic responses of a Gram-negative to an antibiotic that render it immune to an antibiotic are also discussed. Lastly, the methods that have been developed for the identification of bacteria that over-express their EP system are presented in detail. Phenothiazines are well-known antipsychotic drugs with reported activity against bacterial EPs and other ancillary antibiotic mechanisms of the organism. Therefore these compounds will also be discussed.